Community Land Trusts: Permanently Affordable, Resident-Controlled Housing - Stocking, Fred (Maine Policy Review, 1999)
Since 1997 Maine has enjoyed one of the highest levels of home ownership in the country. As Fred Stocking points out, homeownership contributes to community stability and provides a sense of security to families. Yet not all of Maine families are able to achieve their dream of homeownership. Community Land Trusts (CLTs) represent an attempt to build community and solve an affordable housing problem for Maine’s low-income residents. CLTs are non-profit organizations that require the joint involvement of residents and non-residents in the housing development and management, and resale price restrictions that keep the housing affordable indefinitely. In this article Stocking outlines the history of the Community Land Trusts in Maine and provides several examples of successful CLTs in communities such as Bangor, Augusta, and Isleboro. Stocking argues that CLTs make wise use of scarce housing subsidy dollars, encourage residents and community members to work together, and offer an alternative to reliance on broad-based programs administered by the federal government.